2021
DOI: 10.4414/smw.2021.w30089
|View full text |Cite
|
Sign up to set email alerts
|

HCV RNA quantification in capillary dried blood spots with the Xpert® HCV Viral Load test for diagnosing chronic HCV infection, monitoring treatment and detecting reinfection

Abstract: BACKGROUND: For patients with difficult venous access after long-term intravenous drug use, rapid point-of-care hepatitis C virus (HCV) RNA quantification in capillary whole blood with the Xpert® HCV Viral Load Fingerstick (VL FS) test (60 minutes) is a convenient and reliable method for diagnosing chronic HCV infection, monitoring treatment and detecting reinfection. However, an expensive GeneXpert® system must be available on site. In decentralised settings with a low case-load, dried blood spot (DBS) testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Even after volume (DPS)-Hc/volume (DBS) correction, VL values in dried samples vary when compared to plasma, as previously reported ( 52 , 54 ). In our study, compared to plasmatic VL, corrected HCV VL in DPS was more accurate than DBS after immediate processing (t0) (VL average difference of 0.3 log 10 IU/mL vs 0.5 log 10 IU/mL).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Even after volume (DPS)-Hc/volume (DBS) correction, VL values in dried samples vary when compared to plasma, as previously reported ( 52 , 54 ). In our study, compared to plasmatic VL, corrected HCV VL in DPS was more accurate than DBS after immediate processing (t0) (VL average difference of 0.3 log 10 IU/mL vs 0.5 log 10 IU/mL).…”
Section: Discussionsupporting
confidence: 60%
“…Molecular POC tests for HCV RNA detection present excellent accuracy for hepatitis diagnosis ( 38 , 51 ). Previous studies have shown that HCV RNA can be reliably detected and quantified with the molecular POC Xpert HCV VL test in DBS with sensitivities around 90% ( 38 , 42 , 52 ). In this study, we found maximum (100%) sensitivity and specificity by Xpert HCV VL in DBS and DPS after immediate processing (t0) even before volume (DPS) or hematocrit (Hc) and volume (DPS) corrections, demonstrating excellent reliability in both samples for HCV POC RNA detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation